2017
DOI: 10.1161/jaha.117.005676
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Atherosclerotic Cardiovascular Disease Pooled Cohort Risk Equations by Social Deprivation Status

Abstract: BackgroundThe atherosclerosis cardiovascular disease (ASCVD) Pooled Cohort risk equations have shown different calibration across US populations with varied levels of social deprivation.Methods and ResultsWe analyzed the calibration and discrimination of the Pooled Cohort risk equations by social deprivation status among 9066 REGARDS (REasons for Geographic And Racial Differences in Stroke) study participants not taking statins for whom ASCVD risk may lead to statin initiation. Patients were aged 45 to 79 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…Overprediction of risk may be more pronounced in income strata such as individuals with higher socioeconomic status. 30 Much of the difference by cohort should be captured in the risk factors included in the equations; if not, 18 this suggests that the equations may be improved by including additional factors. A recently proposed revision of the pooled cohort equations using more contem-porary cohort data and new derivation methods appeared to improve the accuracy of ASCVD risk estimates 31 but will require additional validation, including assessment of accuracy with and without inclusion of CMS-identified events.…”
Section: Discussionmentioning
confidence: 99%
“…Overprediction of risk may be more pronounced in income strata such as individuals with higher socioeconomic status. 30 Much of the difference by cohort should be captured in the risk factors included in the equations; if not, 18 this suggests that the equations may be improved by including additional factors. A recently proposed revision of the pooled cohort equations using more contem-porary cohort data and new derivation methods appeared to improve the accuracy of ASCVD risk estimates 31 but will require additional validation, including assessment of accuracy with and without inclusion of CMS-identified events.…”
Section: Discussionmentioning
confidence: 99%
“…Whether knowledge of the enrolled MESA subjects’ coronary artery calcium score led to activities to reduce risk is not clear 51. The Atherosclerotic Cardiovascular Disease score accurately predicted risk in the Reasons for geographic and racial differences in stroke, a contemporary US dataset that includes representative ethnicity and socioeconomic status 52. A recent study in stable INOCA patients undergoing Coronary Reactivity Testing (CRT) demonstrated that a majority were classified as intermediate risk by FRS, which did not accurately predict MACE, while the addition of coronary macro‐ and microvascular endothelial dysfunction to the FRS correctly reclassified 23%, with a net reclassification index of 0.23 53.…”
Section: Primary Prevention Risk Scoresmentioning
confidence: 99%
“…We sought to evaluate differences in predicted HF risk across key sociodemographic strata. While both predicted and actual CVD events vary by education and living status, income level, and living environment [26,27], the role of these sociodemographic factors in predicting incident HF remains largely unexplored. Low socioeconomic status, and its correlates, including low educational attainment, are independent risk factors for CVD events, including non-fatal myocardial infarction and sudden cardiac death, in both men and women [28].…”
Section: Discussionmentioning
confidence: 99%